THE CORRELATION BETWEEN IRON DEFICIENCY ANEMIA AND NUTRITIONAL STATUS IN TODDLERS AT UNS HOSPITAL - Muhammad Iqbal Albashiry; Maria Galuh Kamenyangan Sari; Siti Munawaroh; Debby Andina Landiasari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Anemia occurs in 1 in 3 toddlers in Indonesia. Iron deficiency anemia (IDA) is one of the most common causes of anemia in toddlers. Iron deficiency affects the synthesis of DNA, neurotransmitters, and mitochondrial cytochrome. Lacking nutrition can cause health problems in toddlers. This is characterized by the nutritional status of toddlers classified as short or underweight. This study aims to determine the correlation between IDA and nutritional status in toddlers.Method: This research is an analytical observational study with a cross sectional approach. The population for this study were toddlers who had been treated at UNS Hospital from 2021 to 2023. The samples in this study were taken using purposive sampling, totaling 115 toddlers. The independent variable is IDA and the dependent variable is the toddler's nutritional status. Data analysis used the Spearman test with SPSS version 25.Result: This study showed 75 IDA toddlers and 40 others had normal hemoglobin. The toddlers were tested with 2 z-score indicators. The highest number of test results with the Weight/Length indicator was -2SD to 2SD (good nutrition) with a total of 87 toddlers and the Length/Age indicator was -2SD to 2SD (normal) with a total of 67 toddlers. It was analyzed using the Spearman test and a significant value of 0.235 for the Weight/Length indicator and 0.140 for the Length/Age indicator. Both indicators show results of more than 0.05 (p > 0.05).Conclusion: There is no significant correlation between iron deficiency anemia and nutritional status in toddlers at UNS Hospital.